DESAIN DAN UJI COBA MODUL BERBASIS POE (PREDICT-OBSERVE- EXPLAIN) PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Hardianti Rukmana; Lisa Utami (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2020)
This research was instigated by the problem of the lack of variety of media develoved in school, that why, it was designed and testing POE (Predict-Observe-Explain) Based Module on Electrolyte and non-Electrolyte Solution lesson. 4-D development model was used in this research until develop stage. The subjects of this research were an Expert of Material, an Expert of Media, 3 teachers to test media practicality and 12 students of State Senior High School for knowing the respond to media. The method of collecting the data was questionnaire sheet that was analyzed by using Qualitative and Quantitative Descriptive. Based on the research finding, it was obtained that the percentage of media validity by the expert media was 89.15% and it was on very valid criterion. The assessment percentage of students practicality test and teacher was 94.5% and it was on very practical criterion.